2011
DOI: 10.1007/s10389-011-0429-z
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and patient-reported quality of care: an evaluation of the primary care based German disease management program for type 2 diabetes

Abstract: Aims Previous evaluations of the German disease management program (DMP) for type 2 diabetes show that this approach curbs drug and hospital costs, may reduce mortality and improve quality of diabetes care. Otherwise until now there have been no evaluations which analyse the impact of comorbidity (COMORB) on the effectiveness of German DMP to strengthen patient-reported quality of care. Therefore, the study aimed to assess and compare the impact of comorbidity on patient-reported quality of care for patients p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The results of this population-based study show that people with a diagnosed diabetes in the past twelve months assess the quality of the care they receive as moderate. Previous studies examining this indicator carried out in Germany have been based on clinical and regional study populations [ 15–18 ]; they found a similar or slightly better rating of quality of care than in the present study. Differences in the study design and the version of the PACIC questionnaire used mean that these results are only comparable to a limited extent.…”
Section: Resultssupporting
confidence: 73%
“…The results of this population-based study show that people with a diagnosed diabetes in the past twelve months assess the quality of the care they receive as moderate. Previous studies examining this indicator carried out in Germany have been based on clinical and regional study populations [ 15–18 ]; they found a similar or slightly better rating of quality of care than in the present study. Differences in the study design and the version of the PACIC questionnaire used mean that these results are only comparable to a limited extent.…”
Section: Resultssupporting
confidence: 73%
“…Diabetes, a frequent chronic disease with an increasing prevalence, is often the target of integrated care initiatives . The PACIC and PACIC‐5A have often been used as instruments for the evaluation of these initiatives . Within such studies, the PACIC and PACIC‐5A are more frequently used than the ACIC; indeed, the latter is directed at HCPs at the organizational level and does not allow a direct comparison between patients and individual HCPs.…”
Section: Introductionmentioning
confidence: 99%